The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/0104-6632.20150321s00002662
|View full text |Cite
|
Sign up to set email alerts
|

ENANTIOPURE R(-)-3-AMINOISOBUTYRIC ACID SYNTHESIS USING Pseudomonas aeruginosa AS ENANTIOSPECIFIC BIOCATALYST

Abstract: -The main goal of this research was the synthesis of enantiopure R(-)-3-aminoisobutyric acid from dihydrothymine with good yield, high stereospecificity and relative simplicity. Seventy two percent yield of the product was obtained in three steps.Step one consisted of dihydrothymine racemization.Step two was a dihydropyrimidinase reaction involving the Pseudomonas aeruginosa 10145 bacterial strain as the biocatalyst.Step three was performed with a diazotization reaction. The bacteria's enzymes determined the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…We first set up a one-pot cascade reaction with benzyl 3oxobutanoate, using similar conditions as those used for 3-OTfBE (see Figure 6), as it was one of the preferred β-keto esters for both hydrolase and transaminase reactions from those seven tested, and the possible end β-amino acid product of the reaction is an important intermediate for the production of biomedicals. [36] The products were quantified using HPLC. We found that the β-keto ester benzyl 3oxobutanoate (concentration, 14 mM) was converted to a high extent (> 95 % after 20 min and 99 % after 60 min; Figure S15).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first set up a one-pot cascade reaction with benzyl 3oxobutanoate, using similar conditions as those used for 3-OTfBE (see Figure 6), as it was one of the preferred β-keto esters for both hydrolase and transaminase reactions from those seven tested, and the possible end β-amino acid product of the reaction is an important intermediate for the production of biomedicals. [36] The products were quantified using HPLC. We found that the β-keto ester benzyl 3oxobutanoate (concentration, 14 mM) was converted to a high extent (> 95 % after 20 min and 99 % after 60 min; Figure S15).…”
Section: Methodsmentioning
confidence: 99%
“…[22,23] Simulation of the reaction by a local PELE exploration showed efficient 3-ATfBE and 3-OTfBE catalytic (hydrolytic) binding poses: 23 catalytic events for 3-ATfBE and 42 for 3-OTfBE when the serine-substrate distance threshold was set to 4 Å (Figure S12). Glyceryl tripropionate, an example of an ester commonly hydrolyzed by most esterases, [36] had 121 catalytic events with an associated experimental k cat of 388.1 min À 1 (Table S5). Thus, we expected that 3-OTfBE would be preferentially hydrolyzed.…”
Section: Substratementioning
confidence: 99%